Quand la collaboration de recherche sert la légitimation d'un savoir d'expérience - Serge Desgagné; Hélène Larouche (Nantes Université, 2010)
In this article, we discuss collaborative research with teachers as it can provide legitimacy to their practical knowledge. We illustrate this by describing a research program which aims at producing exemplary stories of teaching practices that are intended to be used in teacher education activities, according to the case method. In the description of the research, we raise some important issues in the process of legitimatization to each of the phases of exemplary stories: reconstruction (phase 1), analysis (phase 2) and use for teacher education (phase 3). The third phase in particular is highlighted as it establishes our current area of research, regarding the appropriation of the practical knowledge by student teachers and showing how exemplary stories can play a mediation role in teacher education activities.